Apendicite epiplóica: resolução videolaparoscópica - Silva,Ivan Tramujas da Costa e (2005)
Appendices epiploicae can be the site of torsion and appendagitis. Diagnosis is currently being made by ultrasonography and computerized tomography. Expectant treatment is proposed based on the assumption that epiploic appendicitis is a self limited affection. A case of torsion of a sigmoid epiploic appendage is described. The condition was missed by abdominal ultrasonography. Correct diagnosis and immediate definite treatment were performed by videolaparoscopy.